“Broken” English as an Emotional Language in Amy Tan's “Mother Tongue” - Kandel, Churamoni (Haimaprabha, 2026)
This research article examines and analyzes the role of “broken” English as an emotionally expressive and meaningful language in Amy Tan’s essay “Mother Tongue”. It explores the affective dimension of nonstandard English. It makes a study how Tan represents her mother’s language as a medium of intimacy, relational understanding, and cultural identity. It employs a qualitative research design to make a close textual analysis of selected passages, and focuses on narrative tone, diction, imagery, and contextualized dialogue. By doing so, it reveals the emotional richness of what people often termed as “broken”. The analyses portray how Tan’s mother’s English conveys feelings, perceptions, and shared meaning effectively, despite not conforming to standard grammatical norms. These perspectives postulate how societal judgments often marginalize nonstandard speakers while overlooking the emotional and communicative strength of their language. This research foregrounds the emotional expression to portray Tan’s mother’s English as a legitimate form of communication. This claim helps to shape both family dynamics and her literary voice. The findings of the study contribute to literary, sociolinguistic, and educational discourses as grammar solely does not determine the meaning, clarity, and narrative power. Employing the theoretical frameworks like language ideology, symbolic power, identity construction, language and emotion studies; this research finds nonstandard English as a legitimate and emotionally powerful form of communication. These frameworks contribute to broader discussions of language, identity, and cultural representation.